Economy of Latin America and the Caribbean : guidelines for a comprehensive approach to the foreign debt problem and possible action by the inter-American system (OAS. General Secretariat Washington DCUS, 1986)
Summarizes views that are not strictly financial, for analyzing foreign debt problem. Discusses financial crisis as it relates to recession, a drop in prices of raw materials, and other external conditioning factors. Examines management of financial crisis and economic trends in the region in 1985. Outlines main features of a new approach to the crisis which includes adapting the development strategy to a changing world, creating a favourable external policy environment, and a multi-faceted action plan by the inter-American system.
Includes bibliographical references